Application of the Naive Bayes Method in Diagnosing Diseases of Garlic Plants - Oktavia, Yuke; Kanedi , Indra; Sapri , Sapri (Jurnal Komputer Indonesia, 2022)
To avoid crop failure, of course, insight and knowledge is needed about garlic plant diseases, where there are 7 diseases found in garlic, namely fusarium wilt, leaf tip death, powdery mildew, purple spot, tuber rot, leaf rust, and neck rot. . The limited knowledge of farmers has prompted the Department of Food Crops, Horticulture and Plantation of the Province of Bengkulu to build a system that can assist in early diagnosing diseases in garlic cultivation. The system in question is an expert system. The application of an expert system for diagnosing garlic plant diseases at the Department of Food Crops, Horticulture and Plantation of Bengkulu Province is used to make it easier for users to find out garlic plant diseases based on the symptoms that have been selected. In this application, the Naive Bayes method has been applied to represent, combine, and propagation of uncertainty, which has several intuitive characteristics according to the way of thinking of an expert. Of course, this will speed up the handling of garlic plants if the disease that attacks the plant is known earlier. The application of an expert system for diagnosing garlic plant diseases is made using the Visual Basic .Net programming language and SQL Server database. Based on the system testing that has been done, it can be concluded that the functionality of the application has been running well and this expert system can provide consultation results based on the symptoms selected through the stages of the Naive Bayes method.